DataSheet1_Health Outcomes in EU Cross-Border Regions: A Scoping Review.docx - Sophie Stroisch (20771870) (2025)
Objective This scoping review examines health outcome trends in European cross-border regions, identifies available evidence, and highlights research gaps. The European Union’s integration efforts aim to harmonise living standards and healthcare access. Removed border controls and freedom of movement enhanced service availability, benefiting populations in border regions with cross-border healthcare access. However, these populations are exposed to different institutional settings, highlighting health differences worth studying. Methods We employed the Joanna Briggs Institute methodology, using the PCC (Population-Concept-Context) framework to set eligibility criteria. The search covered literature databases and international governmental institution websites, yielding 785 studies, with 24 included in the final analysis. Results No comprehensive studies investigating longitudinal population health patterns were found. Instead, there are studies on specific diseases or health outcomes in particular border regions, especially around Germany. Most of these studies were cross-sectional. Five key research themes emerged: antibiotic resistance, COVID-19/SARS-CoV-2, other infectious diseases, cancer survival, and additional health outcomes. Conclusion The findings suggest that cross-border contexts have predominantly been used to study infectious disease spread, with little attention given to the broader impact of European integration on long-term health trends.